2014
DOI: 10.5901/mjss.2014.v5n14p521
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Participatory Development: A Case for Communicative Ethics

Abstract: Participatory development has long been touted as a panacea to the development failures resulting from highly burecraticesd and top down development programmes instituted by international donor agencies (Jennings, 2000;Neef, 2003;Mohan, 2001;Cleaver, 1999)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Numerous benefits are perceived to derive from participatory development. For instance, the UNDP (2012a) report identifies some core benefits of participation (Drysdale & Purcell, 2005;Osikhena & Chikadzi, 2014). Generally, participation in the view of Finsterbusch and Van Wicklin III (1989) is seen as enhancing four basic benefits in particular.…”
Section: Participatory Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous benefits are perceived to derive from participatory development. For instance, the UNDP (2012a) report identifies some core benefits of participation (Drysdale & Purcell, 2005;Osikhena & Chikadzi, 2014). Generally, participation in the view of Finsterbusch and Van Wicklin III (1989) is seen as enhancing four basic benefits in particular.…”
Section: Participatory Developmentmentioning
confidence: 99%
“…Duraiappah, Roddy, and Parry () have suggested that PRA as a participatory approach also assists researchers to learn about communities in addition to developing relevant interventions communities. PRA is effective in cooperating with the subject communities to evaluate their constraints and the prospects that can have an impact on them, hence assisting to make decisions regarding development projects (Osikhena & Chikadzi, ).…”
Section: Approaches and Tools To Participatory Developmentmentioning
confidence: 99%
See 3 more Smart Citations